Variation in the Permeability of Intact and Fractured Rocks due to Transient Disturbances in Axial Stress or Pore Pressure - Sophea Boeut; Teppei Oshima; Yoshiaki Fujii; Jun-ichi Kodama; Daisuke Fukuda; Hiroyuki Matsumoto; Kazumi Uchida; Anjula B. N. Dassanayake (Advances in Civil Engineering)
A persistent increase in the permeability of rock mass caused by transient stress disturbances, if present, could explain the variation in the groundwater level in far fields, increase in petroleum production caused by earthquakes or artificial vibrations in enhanced oil recovery, and induction of earthquakes by seismic waves in intermediate and far fields. However, it has not been verified whether the transient stress disturbances induce an increase or decrease in the rock permeability. In this study, the permeability values of intact and triaxially fractured Kushiro Cretaceous sandstone and Shikotsu welded tuff were measured before and after transient axial stress or pore pressure disturbances to clarify the effects of transient stress disturbances on rock permeability. According to the experimental results, the stress disturbances showed either decreasing or increasing effects on the permeability depending on the rock type and experimental conditions. However, when focusing on the fractured rocks rather than the intact ones, which would be more important in field applications, the argillaceous Kushiro Cretaceous sandstone mainly exhibited decreasing effects and the glassy Shikotsu welded tuff mainly exhibited increasing effects.